Research progress of extended care in elderly patients with chronic diseases (老年慢性病患者延续性护理的研究进展) - BI Xiaolu (毕晓露); DENG Ying (邓颖) (Association of Integrative Nursing, 2024)
The extended care service plays an important role in improving the condition and quality of life of elderly patients with chronic diseases. This paper introduced the concept of extended care, and summarized the ways of extended care service for elderly patients with chronic diseases in China. This paper also concluded the nursing quality assessment and limits in research of extended care for chronic diseases in the elderly, and provided reference for the future research direction and establishment of extended care program for elderly patients with chronic diseases in China. (延续性护理服务对改善老年慢性病患者病情、提高生活质量具有重要的作用。本文就当前国内关于老年慢性病延续护理的相关护理模式、护理质量评估及局限性进行综述, 以期为新形势下制定我国老年慢病患者延续护理服务提供参考。)